Identification of Toxoplasma gondii antigenic proteins using an in vivo approach and in silico investigation of their polymorphism - J. Denis; C. Gommenginger; L. Beal; B. Cimon; A. S. Deleplancque; H. Fricker Hidalgo; C. L'Ollivier; L. Paris; H. Pelloux; C. Pomares; S. Houze; A. W. Pfaff; et al. (Microbiology Spectrum)
ABSTRACT Toxoplasma gondii is a pathogen characterized by a large variety of strains whose virulence and clinical severity are likely linked to their genotype. Currently, the strains are genotyped using restriction fragment length polymorphism, multilocus sequence typing, and microsatellite markers. This typing requires the strain’s DNA, which is difficult to obtain. A serotyping test could overcome the constraints of genotyping, the challenge being to identify type-specific proteins. We identified immunogenic T. gondii proteins from co-immunoprecipitations for three tachyzoite strains (strain FOU from Africa 1 type, ME49 from Type II, and VEG from Type III) with hyperimmune murine sera and conducted an in silico polymorphism search for the identified proteins. A variant calling analysis was conducted on the next-generation sequencing sequences of 117 T. gondii isolates with the objective of identifying mutations present in the genes encoding the antigenic proteins previously identified. A total of 727 immunogenic proteins were identified, including 16% dense granule protein (GRA), rhoptry protein (ROP/RON), and surface antigen protein (SAG). Genetic analysis revealed the presence of 36 single-nucleotide polymorphisms (SNPs) in over 70% of isolates belonging to the same type, while less than 30% of isolates belonging to the other types exhibited these polymorphisms. Of these, only 15 are located on coding DNA sequence regions, while four are located on genes encoding apicomplexan proteins: two SNPs on the ROP5 gene and two on the ROP7 gene. The results of this study indicate that a significant number of T. gondii immunogenic proteins can be identified using an in vivo approach. The in silico study identified SNPs that could be genotype-specific.IMPORTANCEToxoplasma gondii is a unique species that exhibits genotype diversity related to clinical virulence. Currently, genotyping is restricted, which limits epidemiological knowledge of the strains. To overcome this limitation, we aimed to develop serotyping tests. First, we used a murine in vivo, non-targeted experimental approach based on proteomics techniques through which we were able to identify a panel of more than 700 antigenic proteins from T. gondii. Then, we analyzed the polymorphism of these proteins using a whole-genome sequencing database containing the genomes of 117 genotyped strains. We showed that none of the 986 non-silent SNPs detected is specific to the strain type. The in vivo approach is the first that allowed the identification of such a large panel of antigenic proteins. Moreover, the polymorphism analysis, the first based on a large next-generation sequencing database, showed the limits that currently restrict the development of a serotyping technique.